Retrospective analysis of the microbiological spectrum of pneumonia in Turkish patients with lung cancer - Avcı, Nilüfer; Hartavi, Mustafa; Kaçan, Turgut; Bayındır, Murat; Avcı, Mustafa; Özakın, Cüneyt; Engin, Aynur; Deliqönüll, Adem; Evrensel, Turkkan; Akalın, Halis (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: The spectrum of pulmonary infections in patients with lung cancer is wide, and tools for target-oriented infection control measures are necessary. In this retrospective study we report the microbiological spectrum of pneumonia (based on the results of sputum culture) in a case series of Turkish patients with lung malignancies. Material and methods: Between 2010 and 2011 a total of 119 patients (111 males and 8 females, mean age: 59.8 ±9.6 years) with lung cancer and pneumonia were identified at the Department of Medical Oncology of two Turkish Universities (Uludag University, Bursa and Cumhuriyet University, Sivas). Expectorated sputum samples were collected in sterile specimen containers and processed immediately in the hospital bacteriology laboratory. Results: Of the 119 study patients, 92 (77.3%) had positive isolates from sputum cultures. The most frequent isolate from the sputum of lung cancer patients with pneumonia was Aspergillus fumigatus (n = 22), followed by Haemophilus influenzae (n = 13) and Pseudomonas aeruginosa (n = 12). The likelihood of having a positive Aspergillus fumigatus sputum culture was significantly and independently associated with febrile neutropaenia (OR = 1.32, 95% CI: 1.17–3.68, p < 0.05) and the development of pneumonia within the first 10 days of chemotherapy initiation (OR = 1.78, 95% CI: 1.37–4.12, p < 0.01). Conclusions : We conclude that Aspergillus fumigatus was the most frequent isolate, but the high diversity of pathogens clearly challenges the empirical use of antimicrobial drugs.